A Brighton Collaboration standardized template with key considerations for a benefit/risk assessment for the Moderna COVID-19 Vaccine (mRNA-1273). Issue 35 (19th August 2022) - Leav, Brett; Straus, Walter; White, Phil; Leav, Alison; Gaines, Tashawnee; Maggiacomo, Grace; Kim, Denny; Smith, Emily R.; Gurwith, Marc; Chen, Robert T.; ,
Abstract: The Brighton Collaboration Benefit-Risk Assessment of VAccines by TechnolOgy (BRAVATO) Working Group has prepared standardized templates to describe the key considerations for the benefit-risk assessment of several vaccine platform technologies, including nucleic acid (RNA and DNA) vaccines. This paper uses the BRAVATO template to review the features of a vaccine employing a proprietary mRNA vaccine platform to develop Moderna COVID-19 Vaccine (mRNA-1273); a highly effective vaccine to prevent coronavirus disease 2019 (Covid-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In response to the pandemic the first in human studies began in March 2020 and the pivotal, placebo-controlled phase 3 efficacy study in over 30, 000 adults began in July 2020. Based on demonstration of efficacy and safety at the time of interim analysis in November 2020 and at the time of trial unblinding in March 2021, the mRNA-1273 received Emergency Use Authorization in December 2020 and full FDA approval in January 2022.